HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA TENTANG EFEK ROKOK DENGAN PERILAKU MEROKOK REMAJA DI KELURAHAN KRAMAT KECAMATAN SENEN JAKARTA PUSAT - Dessi Purnamasari; Miftahul Rasyad; Arni Safdiantina (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2020)
Indonesia is a developing country that has a high level of consumption and production of cigarettes. In fact, the variety of products and prices of cigarettes in Indonesia has placed Indonesia as one of the largest producers and consumers of cigarettes in the world. This study aims to determine the relationship between the level of knowledge and attitudes of adolescents about the effects of smoking related to smoking behavior of adolescents in RT 004/RW 03 Kel. Kramat, Kec. Monday, Central Jakarta. This study used an analytical survey method with a cross sectional study design with a sample of 20 teenagers. The results showed that as many as 58.3% of adolescents aged 17-21 years smoked and this was the highest percentage. Based on the chi-square test, there were 2 variables that were significantly related to smoking behavior in adolescents, namely the level of knowledge and attitudes of adolescents, which obtained a P value of 0.005 (P value ).